Correlation of the plasmon-enhanced photoconductance and photovoltaic properties of core-shell Au@TiO2 network - Yang, Yiqun Q.; Wu, Judy; Li, Jun (My University, 2016)
This study reveals the contribution of hot electrons from the excited plasmonic nanoparticles in dye sensitized solar cells (DSSCs) by correlating the photoconductance of a core-shell Au@TiO2 network on a micro-gap electrode and the photovolatic properties of this material as photoanodes in DSSCs. The distinct wavelength dependence of these two devices reveals that the plasmon-excited hot electrons can easily overcome the Schottky barrier at Au/TiO2 interface in the whole visible wavelength range and transfer from Au nanoparticles into the TiO2 network. The enhanced charge carrier density leads to higher photoconductance and facilitates more efficient charge separation and photoelectron collection in the DSSCs. Published by AIP Publishing.
Citation: Yang, Y. Q., Wu, J., & Li, J. (2016). Correlation of the plasmon-enhanced photoconductance and photovoltaic properties of core-shell Au@TiO2 network. Applied Physics Letters, 109(9), 5. doi:10.1063/1.4961884
Keywords: Sensitized Solar-Cells; Gold Nanoparticles; Tio2 Films; Resonance; Nanostructures; Photocurrent